Formação profissional em serviço social nas instituições de ensino superior: caminhos pedagógico-ético-político em questão - São Paulo/SP, 2010 - Guimarães, Jayson Vaz (2010)
This thesis consists of an investigative process, whose objective was to understand and analyze the relationship between the PPP of Social Work courses and four IES PEPPSSB in the process of training of the Social Worker in Sao Paulo in 2010. The research was a central issue: how to express themselves and relate to the PPP and PEPPSSB in the process of training of the Social Worker at graduation? To answer, and provisionally assumed this question, I elaborated the hypothesis that in Social Work courses at IES in São Paulo / SP relationships exist convergence in Education and Social Services, about the design of training emancipatory, referenced in the matrix critical social theory, albeit with different theoretical perspectives. These strands in the operationalization and implementation of PPP guided by PEPPSSB brings distinct implications for teaching and learning process. These relations between the PPP and PEPPSSB express contradictions, empowered by the IES of PDI, business character. The research had as reference the central theoretical and methodological perspective on the dialectical approach of the Marxist tradition, choosing as main categories: all, contradiction and mediation. The conceptual references are in contemporary authors primarily in the areas of Education and Social Work. The methodology that guided the research was based on the principles of investigation, of quanti covered the landscape of higher education in São Paulo, in which there are 18 private higher education institutions with courses in Social Work. The methodological procedures included the use of bibliographical research, questionnaires and focus group interviews with people involved in this process: engineers, teachers and students. The historical background covered the debate on the Brazilian scene of higher education and vocational training in social work in dialogue with the PPP. Analysis, in summary, the PPP of IES surveyed, although drawn from the DCN ABEPSS was a perceived distancing of PEPPSSB, since the operation of the PPP has its corporate-type management, coordinators, teachers and students are located between the desire, the real opportunities and challenges for the deployment of an emancipatory nature of PPP. To cope with these dilemmas is necessary to break with the design of the arrays and fragmented disciplinary curriculum for working with educational arenas that have as main organizers of learning designs originated in the concrete reality of the environment in which they live